The Effect of Anxiety and Self-confidence on Arabic Speaking Proficiency in the International Class Program (ICP) - Ratni Bt Hj. Bahri; Ibnu Rawandhy N. Hula; Nurul Aini Pakaya; Musdelifa Abu Samad; Yousif Abdelmannan Mohamed Godat Arrashedy (Alsina : Journal of Arabic Studies, 2026)
This study aims to analyze the influence of anxiety and self-confidence on Arabic speaking proficiency among students in face-to-face learning in the International Class Program (ICP), and to examine the direct contributions of both psychological variables to speaking performance. Using a quantitative survey design, 148 second-semester ICP students at IAIN Sultan Amai Gorontalo participated in the study. Data were collected through questionnaires and an oral speaking assessment, and were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The results show that the highest anxiety indicator was frustration during live dialogue/discussion (83.8%), followed by panic when speaking (72.3%) and increased heart rate when asked to speak (71.6%). The lowest self-confidence indicator was speaking confidence (35.3%), although tolerance for making mistakes was relatively high (65.0%). In terms of speaking performance, the highest mean scores were found in fluency (78.25) and vocabulary usage (77.10), while grammar mastery had the lowest mean score (73.80). Correlation analysis showed that anxiety was negatively associated with all speaking indicators (r = –0.52 to –0.58), whereas self-confidence was positively associated with all speaking indicators (r = 0.44 to 0.49). SEM analysis showed significant direct effects: anxiety had a negative effect on Arabic speaking proficiency (β = –0.55, p < 0.001), while self-confidence had a positive effect (β = 0.47, p < 0.001). However, the model did not test a moderation effect; therefore, self-confidence cannot be interpreted as a statistically confirmed moderator. Overall, the findings indicate that anxiety and self-confidence are important psychological predictors of Arabic speaking proficiency and should be considered in the design of face-to-face Arabic learning in international classroom settings.